Interior strain analysis of a woven composite beam using X-ray computed tomography and digital volumetric speckle photography. (15th December 2015) - Mao, Lingtao; Chiang, Fu-pen
Abstract: Materials such as fiber reinforced composite are inherently 3D in nature. Its internal stress/strain fields are very complex even under the simplest loading condition. There is no effective means of measuring interior strain other than placing isolated sensors. In this paper we introduce a new strain measuring technique called digital volumetric speckle photography whereby we can probe the interior strain field in a whole field manner. We apply it to the determination in a woven fiber composite beam under 3-point bend. The in-plane strain field of three transverse sections and two longitudinal sections are determined using the technique. In addition we show that one of the principal strain fields of the mid-longitudinal section tends to predict the impending failure of the beam.